L-Theanine attenuates oxidative damage induced by heat stress through the PI3K/AKT/Nrf2 signaling pathway in skeletal muscle cells - Qiong Wu; Xiaochun Wan; Dongxu Wang; Mingqi Ma; Xinru Hu; Xingyong Chen; Xiaoling Ding; Cheng Zhang (Poultry Science)
The rising prevalence of heat stress (HS), because of global warming, presents a considerable challenge to both human and animal health and welfare. L-Theanine (LTA), a naturally occurring amino acid, may enhance poultry muscle yield and quality, suggesting its potential application in alleviating the negative impacts of HS. However, the molecular mechanisms through which LTA exerts its beneficial effects remain to be fully understood. This study explored the protective effects of LTA on cultured broiler skeletal muscle cells under oxidative stress induced by HS, focusing on the molecular mechanisms involved. Our findings indicate that treatment with LTA significantly improved cell survival, bolstered the activity of antioxidant enzymes, decreased reactive oxygen species (ROS) contents and diminished malondialdehyde (MDA) levels in HS-treated cultured cells. Furthermore, LTA enhanced the phosphatidylinositol 3-kinase (PI3K)/protein kinase B (AKT) and nuclear factor erythroid 2-related factor 2 (Nrf2) signaling pathways in HS-treated cultured cells, facilitating mitochondrial biogenesis and reducing cell apoptosis. The protective effects of LTA in HS-treated cultured cells were significantly reduced by the PI3K inhibitor LY294002 or the Nrf2 inhibitor ML385. In conclusion, our study showed that LTA protects cultured skeletal muscle cells from HS-induced oxidative damage by modulating the PI3K/AKT/Nrf2 signaling pathway, positioning LTA as a promising natural antioxidant for poultry feed additives aimed at improving muscle health.